Effects of Yeast Inoculum Sizes on Fermentation of Petai Belalang Seeds for Coffee-like Beverage Production - Nurul Nadiah, Ahmad Daud (Universiti Malaysia Sarawak (UNIMAS), 2018)
This study focused on Saccharomyces cerevisiae inoculated in different inoculum sizes to investigate which inoculum size is the best for producing the highest starch containing high reducing sugars in optimum time of fermentation. In this experiment, S. cerevisiae or yeast was inoculated from the cultured colony and prepared as five different inoculum sizes in (%v/v); 5%, 10%, 15%, 20%, and 25%. Each inoculum was standardized with 15 ml distilled water and 5 g of mimosinereduced Petai Belalang seeds. For both analysis of starch and protein content, batches without the addition of yeast acted as positive control. Protein content was analysed in relation of production of starch content. The highest starch content was produced by 15% yeast inoculum at 18 h. Next, the content of reducing sugars of fermented, mimosine-reduced Petai Belalang seeds were further analysed using DNS analysis. Before that, the highest and lowest content of starch (based on starch analysis) for each yeast inoculum (%v/v) from 5%, 10%, 15%, and 20% were determined. The result exhibited the highest reducing sugar contents was yielded by replicate labelled C at 18 h of 15% yeast inoculum. Therefore, the replicate was chosen as the best pick to be used for further study of mimosine-reduced Petai Belalang seeds roasting process and were compared with the non-fermented, dried Petai Belalang seeds in terms of colour and aroma.